Oxidation behavior of interstitial free steel: The defining role of substrate crystallographic texture. (15th May 2020) - Mehtani, H.K.; Khan, M.I.; Durgaprasad, A.; Deb, S.K.; Parida, S.; Prasad, M.J.N.V.; Fullwood, David; Doherty, R.D.; Samajdar, I.
Abstract: The oxidation kinetics of interstitial free (IF) steel were shown to differ remarkably, by more than one order of magnitude, with the crystallographic texture of the metallic substrate. More specifically, γ-fiber or ND||<111> grains oxidized preferentially and provided epitaxial or pseudo-epitaxial growth of the corresponding oxide grains. Below 843K, the initial magnetite (Fe3 O4 ) grains had a ∼45°<001> epitaxial orientation relationship with all the substrate ferrite grains. Specimens oxidized at temperature > 843K, on the other hand, had a pseudo-epitaxy: ND||<111> metallic-substrate grains generated ND||<001> pro-eutectoid magnetite. In both cases, the oxide grains growing from ND||<111> ferrite had more dislocations and higher tensile residual stresses. They also had more magnetite and less hematite. It was proposed that the oxide phase growing from ND||<111> ferrite grains, with higher dislocation content, has faster ionic diffusion. Faster diffusion in the magnetite also appeared to reduce the protective (lower ionic diffusion) outer hematite layer. A combination of these two generated thicker oxide layers on the ND||<111> ferrite grains. Graphical abstract: Image, graphical abstract